Degree of polymerization and spatial distributions of acyclic and cyclic oligohexoses in soybean root nodules uncovered by MALDI and nanophotonic laser desorption ionization mass spectrometry - Chloe Corning; Marjan Dolatmoradi; Tina H. Tran; Gary Stacey; Lajos Szente; Laith Z. Samarah; Akos Vertes (Materials Today Bio)
In the symbiotic relationship of legumes and rhizobia, disaccharides, mostly sucrose, are produced by the plant and provided as energy and carbon sources for the bacteria. The microbes, in turn, store these carbohydrates as acyclic oligohexoses to buffer fluctuations in supply. Simultaneously, cyclic oligohexoses (β-glucans) of varying sizes and structures are synthesized by nitrogen-fixing soil bacteria both in free living form and in legume root nodules. In the bacteroids, transformed from Bradyrhizobium japonicum strain USDA110 in soybean (Glycine max) root nodules, glucose units are attached by glycosidic bonds and are known to contain degrees of polymerization with 10 ≤ n ≤ 13 repeat units in branched cyclic structures. Whereas cyclic β-glucans (CβGs) are thought to facilitate bacterial adaptation and legume-rhizobia symbiosis, information on their ring sizes, branching from the ring structures, and their spatial distributions within the nodules is scarce. Here we demonstrate that using mass spectrometry (MS), based on matrix-assisted laser desorption ionization (MALDI) and laser desorption ionization (LDI) from emerging silicon nanopost array (NAPA) nanophotonic platforms, the presence of a wider array of potentially cyclic oligohexoses can be discovered with degrees of polymerization in the 2 ≤ n ≤ 14 residue range. On the low end of the oligomer size distribution, the cyclic nature of CYn with n < 10 can be increasingly questioned based on the large strain such macrocycles would exhibit and the DP control during the CβG synthesis by the glucan phosphorylase involved in their synthesis. At the same time, acyclic oligohexoses with a degree of polymerization of 2 ≤ n ≤ 13 were also detected. Tandem MS with collision induced dissociation (CID) indicated that the cyclic structure with n = 12 contained a branching residue. It detached from the macrocycle at lower collision energies (70 instrument units), whereas the rings themselves fragmented at higher energies (90 instrument units). We also prove that the spatial distributions of acyclic and cyclic oligohexoses in the G. max nodules can be captured by MS imaging (MSI) based on MALDI and NAPA-LDI. The acyclic species were more abundant in the infection zone, whereas the cyclic oligohexoses appeared more concentrated in the inner cortex and in the root vasculature. At some locations, possibly in the vascular bundles surrounding the nodule and traversing the root, the cyclic oligohexoses were especially abundant. The distributions of acyclic oligohexoses were also mapped in the nodule sections. These linear or branching molecules were abundant in the infection zone, where the cyclic oligohexoses were less concentrated or absent.